Commonly prescribed drugs associate with cognitive function: a cross-sectional study in UK Biobank - Nevado-Holgado, A; Kim, C; Winchester, L; Gallacher, J; Lovestone, S (BMJ Publishing Group, 2016)
Objective: To investigate medications associated with cognitive function Design: Population-based cross-sectional cohort study Setting: UK Biobank Participants: UK Biobank participants aged 37-73 years who completed cognitive tests at the baseline visit in 2006-2010 Main outcome measures: Cognitive test outcomes on verbal-numerical reasoning test (n=165493), memory test (n=482766) and reaction time test (n=496813). Results: Most drugs (262 of 368) were not associated with any cognitive tests after adjusting for age, gender, education, household income, smoking, alcohol status, psychostimulant/nootropic medication use, assessment centre and concurrent diagnoses and medications. Drugs used for nervous system disorders were associated with poorer cognitive performance (antiepileptics e.g. topiramate breasoning(score) -0.65 [95%CI: -1.05, -0.24], bmemory(score) -1.41[-1.79, -1.04]; antipsychotics e.g. risperidone breaction time(ms) -33[-46, - 20], negative values indicate poor cognitive performance and vice versa). Drugs used for non-nervous system conditions also showed significant negative association with cognitive score, including those where such an association might have been predicted (antihypertensives e.g. amlodipine breasoning -0.1[-0.15, - 0.06], bmemory -0.08[-0.13, -0.03], breaction time -3[-5, -2]; antidiabetics e.g. insulin breaction time -13[-17, -10]) and others where such an association was a surprising observation (proton pump inhibitors e.g. omeprazole breasoning -0.11[-0.15, -0.06], bmemory -0.08[-0.12, -0.04], breaction time -5[-6, -3]; laxatives e.g. contact laxatives breaction time -13[-19, -8]). Finally, only a few medications and health supplements showed association towards a positive effect on cognitive function (anti-inflammatory agents e.g. ibuprofen breasoning 0.05[0.02, 0.08], breaction time 4[3, 5]; glucosamine breasoning 0.09[0.03, 0.14], breaction time 5[3, 6]). Conclusions: In this large volunteer study, some commonly prescribed medications were associated with poor cognitive performance. Some associations may reflect underlying diseases for which the medications were prescribed, although the analysis controlled for the possible effect of diagnosis. Other drugs, whose association cannot be linked to the effect of any disease, may need vigilance for their implications in clinical practice.